2010
DOI: 10.1373/clinchem.2010.150680
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite Instability Detection by High-Resolution Melting Analysis

Abstract: BACKGROUND:Microsatellite instability (MSI) is an important marker for screening for hereditary nonpolyposis colorectal cancer (Lynch syndrome) as well as a prognostic and predictive marker for sporadic colorectal cancer (CRC). The mononucleotide microsatellite marker panel is a well-established and superior alternative to the traditional Bethesda MSI analysis panel, and does not require testing for corresponding normal DNA. The most common MSI detection techniques-fluorescent capillary electrophoresis and den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 38 publications
0
34
0
Order By: Relevance
“…PCR is used to amplify known microsatellite regions, and the lengths of the short tandem repeats (PCR products) are compared in tumor and normal DNA to determine the state of MSI [37, 67, 68]. This approach is therefore limited to assessing MSI.…”
Section: Methods For the Detection And Analysis Of Genome Instabilitymentioning
confidence: 99%
“…PCR is used to amplify known microsatellite regions, and the lengths of the short tandem repeats (PCR products) are compared in tumor and normal DNA to determine the state of MSI [37, 67, 68]. This approach is therefore limited to assessing MSI.…”
Section: Methods For the Detection And Analysis Of Genome Instabilitymentioning
confidence: 99%
“…An attempt to determine DNA changes indicative of microsatellite instability (MSI) was made using high-resolution melting with primers to NR21, NR22, NR24, BAT25, and BAT26. Using a similar method to that previously described, 14 we analyzed the samples on a Roche LC480. Whereas differences were detected in each of the 5 markers that could be correlated to the IHC results of MSI, we found that the sensitivity and reproducibility of high-resolution melting was not acceptable for clinical testing.…”
Section: Methodsmentioning
confidence: 99%
“…A high-resolution melting (HRM) analysis method was used for detection of two mononucleotide MSI markers – BAT25 and BAT26 [55]. A tumor was defined as MSI when it showed instability with at least one of these markers (BAT25 and BAT26), and as MSS when it showed no instability for both the markers.…”
Section: Methodsmentioning
confidence: 99%
“…In this way, a total of 24 tumor samples showed MSI and all were confirmed by another relatively novel MSI marker CAT25 [56] using HRM analysis. We used published primer sequences [55], [56]. Thermocycling and melting conditions were optimized for CFX96 instrument and Bio-Rad Precision Melt Analysis software was used to identify MSI by differential melting curve characteristics.…”
Section: Methodsmentioning
confidence: 99%